Thermal and growth indices of cayenne pepper (Nhsmb-F4) under optimal and limited water supply regimes - Adekunle, Makinde Akeem; Barakat, Sarumi Oyinkansola; Olayiwola, Eruola Abayomi; Adebayo, Oduwaye Olusegun; Oluwakayode, Ajayi Emmanuel (Canadian Journal of Agriculture and Crops, 2025)
Thermal indices are veritable tools to summarize thermal stress effects on plant growth and yield. This study assessed thermal and growth indices of screenhouse grown pepper under optimal (everyday-T1) and limited water supply regimes (3, 5 and 7 days; T2, T3 and T4 respectively). The study is a factorial experiment in a Complete Randomized Design (CRD) in three replicates. The pepper specie used was Cayenne pepper. Data were collected on the soil, thermal indices: such as Growing Degree Days (GDD), growth parameters (Plant height), phenological events (Days to First Flowering - (DFFL) and Fruit yield. Data collected were subjected to descriptive and inferential statistics (analysis of variance). Treatments means were separated using Least Significance Difference (LSD) at 95 % confidence level. Results of GDD varietal performance under T2 showed that Cayenne pepper accumulated highest GDD (784 °C/day) followed by T4 (495 °C/day) and the least value was observed under T3 (452 °C/day). The GDD values under T2, T3 and T4 were not significantly different (p>0.05) from those obtained under optimal water supply regime (T1). Cayenne pepper plant height under T2 was consistently higher than those under T3 and T4. Phenologically, Cayenne pepper under T3 showed the shortest DFFL. The yield of T2 and T3 were in order of Cayenne pepper (46 and 34 g/pot). The study concluded that, cultivation of Cayenne pepper adapted well to limited water supply regimes of 3, 5 and 7 days without negative effects on the growth and yield in the screenhouse.